Estimation and evaluation of asset pricing models with habit formation using Philippine data - Abara, Raymund R.; Bautista, Carlos C. (Quezon City College of Business Administration, University of the Philippines Diliman, 2004)
This study tests and evaluates the habit-formation model, an extension of the Consumption-based Capital Asset Pricing Model (C-CAPM). Using Philippine equity and Treasury bill data from 1990 to 2003, this study constructs multiple asset porfolios to estimate the parameters of internal and external habit-formation based asset pricing models. Aside from this, additional models are also estimated using de-seasonalized quarterly real consumption together with the C-CAPM. The performance of these resulting models is evaluated in terms of forecast performance both in-sample and out-of sample. Several statistical measures such as the Diebold-Mariano test and the Success Ratio test are used to compare these habit models against the standard power utility/C-CAPM, the random walk with drift model, and the traditional static CAPM. Based on the criteria set by this study, only the external habit model performs better than all the other models.
Research project funded by University through the Office of the Vice-Chancellor for Research and Development (OVCRD).
Thesis (Doctor of Philosophy in Business Administration)--University of the Philippines Diliman
Keywords: Capital assets pricing model; Finance -- Mathematical models